NUDT15 Polymorphisms Alter Thiopurine Metabolism and Hematopoietic Toxicity - Moriyama, Takaya (Nat Genet, 2016)
Widely used as anti-cancer and immunosuppressive agents, thiopurines have narrow therapeutic indices due to frequent toxicities, partly explained by TPMT genetic polymorphisms. Recent studies identified germline NUDT15 variation as another critical determinant of thiopurine intolerance, but the underlying molecular mechanisms and its clinical implications remain unknown. In 270 children enrolled in clinical trials for acute lymphoblastic leukemia in Guatemala, Singapore, and Japan, we identified 4 NUDT15 coding variants (p.Arg139Cys, p.Arg139His, p.Val18Ile, p.Val18_Val19insGlyVal) that resulted in 74.4%–100% loss of nucleotide diphosphatase activity. Loss-of-function NUDT15 diplotypes were consistently associated with thiopurine intolerance across three cohorts (P=0.021, 2.1×10(−5), and 0.0054, respectively; meta-analysis P=4.45×10(−8), allelic effect size=−11.5). Mechanistically, NUDT15 inactivated thiopurine metabolites and decreased its cytotoxicity in vitro, and patients with defective NUDT15 alleles showed excessive thiopurine active metabolites and toxicity. Taken together, our results indicate that a comprehensive pharmacogenetic model integrating NUDT15 variants may inform personalized thiopurine therapy.